Coal burst risk monitoring method based on the drilling powder of destressing drilling in coal seam and its application - Tongbin ZHAO; Yanchun YIN; Wentao REN; Qingzhi ZHANG; Jiuguo GAO; Zhigang ZHAO (Meitan xuebao)
The drilling powder monitoring method is one commonly used method for coal burst risk evaluation in coal mines. The construction method of large-diameter destressing drilling is similar to that of the drilling powder monitoring method. However, due to the lack of drilling powder rate index and efficient weighing method, the drilling powder method based on destressing drilling has not been widely used. Therefore, based on the drilling powder rate index of standard drilling powder monitoring method, one method for determining the drilling powder rate index and the critical powder of large-diameter destressing drilling is proposed, in which its pressure relief effect is considered. By carrying out the laboratory tests of drilling in coal specimens, the functional relationship among the drilling diameter, powder, initial stress and stress after pressure relief is obtained. Then the suggested value of the drilling powder rate index and critical powder of 150mm diameter drilling with 1, 2 and 3 m spacing are obtained. Finally, by using the auto measuring device, the drilling powder of destressing drillings are measured in coal burst risk roadway. The results show that the drilling powder is positively correlated with the drilling diameter and coal stress. Meanwhile, the stress reduction rate after drilling is positively correlated with the drilling diameter-spacing ratio. The drilling powder rate index of 150 mm diameter destressing drilling is higher than that of 44 mm diameter drilling, and the index increases with the decrease of drilling spacing. The drilling powder of 150 mm diameter drilling in 6310 workingface of Tangkou Mine in Shandong is 25−93 kg/m, and there is high stress area at the depth of 12−14 m and 18−20 m from the coal wall. The drilling powder in the gob-side roadway is significantly heavier than that in the solid-coal roadway. Combing the drilling powder rate index determining method and the powder auto measuring device for large-diameter drilling, the coal burst risk monitoring method based on the drilling powder of destressing drilling is developed, which can provide one operative technical approach for the synchronous operation of pressure relief-monitoring in coal burst risk roadway.